Variabel Anteseden Komitmen Sumber Daya Manusia Sektor Publik Berbasis Spirituality - I Made Purba Astakoni; I Wayan Wardita; Ni Made Gunastri; Ni Made Satya Utami; I Nyoman Mustika (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
This study has several purposes namely; analyze the influence of spiritual leadership on workplace spirituality; analyze the influence of spiritual leadership on spiritual survival; analyze the influence of workplace spirituality on an individual spirituality; analyze the influence of spiritual survival on the individual spirituality; analyze an individual spirituality influence on human resource commitments; analyze the role of workplace spirituality and individual spirituality as mediating on the influence of spiritual leadership on human resource commitments and analyze the role of spiritual survival and individual spirituality as mediating on the spiritual influence of leadership on human resource commitments. This study used the population of all employees of drinking water companies in Denpasar, Badung and Tabanan districts as many as 902 employees. The sample number of 200 respondents was done purfosively. Closed multiple-choice questionnaire tools are used for Data collection techniques, and data analysis using the Partial Least Square (PLS) approach. The results showed that the overall evaluation of the model was seen from the side of R-Square (R2), Q-Square Predictive Relevance (Q2) and Goodness of Fit (GoF) then the model was declared good. Of all the hypotheses raised in the model stated all tested significantly and positively.